Maintenance of type 2 glycolytic myofibers with age by Mib1-Actn3 axis - Ji-Yun Seo (Nature Portfolio, 2021)
Muscle atrophy is associated with ageing, but the underlying molecular mechanisms are not well understood. Here, they authors show that ablation of the E3 ubiquitin ligase Mib1 is important for myofibre maintenance via a mechanism that involves targeting and degradation of Actn3, and that Mib1 ablation in mice induces muscle atrophy which can be rescued by knockown of Actn3 expression.